Isokinetic muscle strength profile of ladies professional tour golfers - Seok Won, C.; Byung Wook, S.; Joon Yub, K.; Jae-Young, L.; Sae Hoon, K.; Joo Han, O. (Isokinetics and Exercise Science, 2014)
BACKGROUND: The highly trained professional tour golfers would likely have different strength profiles in their muscle groups from non-athletes, which may be associated with the level of golf performance. OBJECTIVES: To describe an isokinetic muscle strength profile of several upper and lower extremity muscles of ladies professional tour golfers in comparison to non-athlete controls, and to explore possible correlations between strength and driving distance and average score. METHODS: Sixty seven ladies professional tour golfers and 25 non-athletic women were enrolled. Absolute and weight-adjusted concentric isokinetic peak torque (PT) at 60°/s of the shoulder abductors, adductors and rotators, and elbow and knee flexors and extensors were measured bilaterally. RESULTS: All absolute and most weight-adjusted PTs were significantly higher in professional tour golfers than non-athletes. The weight-adjusted PT differed significantly only with respect to the shoulder adductors and knee muscles. Significantly higher strength ratios: bilateral shoulder adductor/abductor, right shoulder internal/external rotator, right elbow extensor/flexor, and bilateral knee flexor/extensor characterized the golfers. Further, the correlations between the strength of any of the tested muscles and either the driving distance or the average score were low to negligible. CONCLUSIONS: These results furnish a reference framework for isokinetic strength of the abovementioned muscles of professional tour golfers, and thus be used in setting realistic rehabilitation goals for lady golfers who suffer from some injury involving, directly or indirectly, these muscles. ABSTRACT FROM AUTHOR